2021
DOI: 10.1093/infdis/jiab229
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Tolerability, and Pharmacokinetics of a Long-Acting Broadly Neutralizing Human Immunodeficiency Virus Type 1 (HIV-1) Monoclonal Antibody VRC01LS in HIV-1–Exposed Newborn Infants

Abstract: Background Perinatal HIV-1 continues to occur due to barriers to effective antiretroviral prevention that might be mitigated by long-acting broadly neutralizing monoclonal antibodies (bNAbs). Methods Extended half-life bNAb, VRC01LS, was administered subcutaneously (SC) at 80 mg/dose after birth to HIV-1-exposed, non-breastfed (Cohort 1, n=10) and breastfed (Cohort 2, n=11) infants. Cohort 2 received a second dose (100mg) at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 38 publications
0
44
0
Order By: Relevance
“…AAVs are non-enveloped viruses that belong to the Parvoviridae family (85,86). AAVs are unable to replicate on their own, and as such require a helper virus, such as an adenovirus or herpesvirus to productively replicate within cells (87)(88)(89)(90). They are composed of an icosahedral protein capsid surrounding a single stranded DNA genome of approximately 4700 base pairs.…”
Section: Utilizing Aav-delivery Of Broadly Neutralizing Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…AAVs are non-enveloped viruses that belong to the Parvoviridae family (85,86). AAVs are unable to replicate on their own, and as such require a helper virus, such as an adenovirus or herpesvirus to productively replicate within cells (87)(88)(89)(90). They are composed of an icosahedral protein capsid surrounding a single stranded DNA genome of approximately 4700 base pairs.…”
Section: Utilizing Aav-delivery Of Broadly Neutralizing Antibodiesmentioning
confidence: 99%
“…The rep gene encodes proteins necessary for virion assembly, including Rep78, Rep68, Rep52 and Rep40. The cap gene encodes for three capsid proteins, VP1, VP2 and VP3 and the assembly activating protein (AAP) and membrane-associated accessory protein (MAAP) in alternative reading frames (87,(92)(93)(94)(95)(96)(97). AAV virions are comprised of 60 VP subunits, and each subunit has nine variable regions that dictate tropism and intracellular trafficking (91).…”
Section: Utilizing Aav-delivery Of Broadly Neutralizing Antibodiesmentioning
confidence: 99%
“…Together with studies in adult subjects, VRC01 (along with VRC01LS and VRC07-523LS neutralizing mAbs) entered ongoing clinical studies involving the study of mother-to-child transmission of HIV-1 (NCT02256631). Preliminary data revealed that subcutaneous VRC01 as single or multiple doses is safe and well-tolerated in very young infants [ 64 ] as well as VRC01LS [ 65 ]. VRC01 efficacy was also tested in HIV-1-infected adults under antiretroviral therapy who experienced a brief analytical treatment interruption (ATI) (NCT02463227).…”
Section: Cd4-binding Site Antibodiesmentioning
confidence: 99%
“…In nonhuman primate (NHP) models of HIV, infection of neonatal and infant rhesus macaques (RM) with simian-human immunodeficiency virus (SHIV) can be prevented by passive administration of broadly neutralizing HIV envelope (Env)-specific antibodies (bNAbs) ( 19 21 ). The use of bNAbs as potential prevention strategy in HIV-exposed infants is supported by results from ongoing clinical trials that indicate that bNAbs (e.g., VRC01) are safe and well tolerated in human neonates ( 22 ). Clinical studies in human adults, however, demonstrated only a minimal risk reduction of HIV infection by preventative treatment with bNAbs ( 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%